PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN PERSEPSI HARGA TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN (Studi pada Konsumen Air Minum dalam Kemasan Aqua di Kota Semarang) (Students' Journal of Economic and Management, 2016)
The purpose of this study was to analyze the influence of brand image, product quality, price perception of customer satisfaction. To analyze the effect of brand image, product quality, perceived price, customer satisfaction to customer loyalty. This research uses seven hypotheses. The population in this study is that consumers buy bottled water Aqua in Semarang. The sample in this study as many as 100 people. The sampling technique used purposive sampling. The criteria for the sample in this study is that consumers purchase and consume bottled water Aqua in Semarang more than twice and domiciled in the city of Semarang. The analysis tool used is multiple linear regression. The results of the analysis can be concluded that: brand image, product quality and price perception positive effect on customer satisfaction. Brand image, product quality, perceived price, customer satisfaction has positive effect on customer loyalty. Satisfaction does not mediate the effect of brand image, product quality and price perception of customer loyalty     Keywords: brand image, product quality, perceived price, customer satisfaction and customer loyalty